2020
DOI: 10.1177/2325967120940958
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal Fluid Extravasation: Is Endoscopic Deep Gluteal Space Exploration a Risk Factor?

Abstract: Background: The extravasation of fluid into the intra-abdominal space is recognized as a possible complication of hip arthroscopic surgery/endoscopy. The exposure of anatomic areas to elevated pump pressures and high volumes of irrigation fluid increases the risk of fluid leakage into anatomic spaces around the hip joint, especially to the abdomen and pelvis. Purpose: To estimate the incidence and risk factors related to intra-abdominal fluid extravasation (IAFE) after hip endoscopy or arthroscopic surgery. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This becomes even more vital when recent studies have shown surgeon perception about intraabdominal fluid extravasation to be as low as 0.16%, compared to an incidence as high as 31.1% when intraabdominal ultrasound scanning is used during surgery. 5,8 Several methods have been proposed to detect the presence of intraabdominal fluid extravasation. Close inspection of the preoperative magnetic resonance image for anatomical variants, particularly between the iliopsoas bursa and hip joint capsule, should alert the surgeon and anesthesiologist for high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This becomes even more vital when recent studies have shown surgeon perception about intraabdominal fluid extravasation to be as low as 0.16%, compared to an incidence as high as 31.1% when intraabdominal ultrasound scanning is used during surgery. 5,8 Several methods have been proposed to detect the presence of intraabdominal fluid extravasation. Close inspection of the preoperative magnetic resonance image for anatomical variants, particularly between the iliopsoas bursa and hip joint capsule, should alert the surgeon and anesthesiologist for high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although the exact cause of IAFE is case dependent, factors that have been found to contribute to increased risk are increased pump pressure, concomitant iliopsoas tenotomy, surgeon experience, and prolonged surgical time. 4,[6][7][8][9] IAFE during arthroscopic hip surgery directly increases intra-abdominal pressure, resulting in intra-abdominal hypertension (IAH). IAH is defined as sustained levels of intra-arterial pressure greater than 12 mm Hg.…”
mentioning
confidence: 99%
“…[18][19][20][21][22] Several complications have been reported with the endoscopic approach, including temporary sciatic nerve injury, hematoma, permanent nerve injury of the posterior femoral cutaneous nerve, 23 and intra-abdominal fluid extravasation. 24 This method does incur a steeper learning curve as well as less direct visualization of the important surrounding neurovascular structures; consequently, entrapment of the sciatic nerve is the leading reported cause of revision surgery. 23 Complications from an endoscopic approach can be severe, and an open approach may reduce the risk of several of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…A positive FAST exam correlates with a minimum of 300 to 500 mL of free fluid in the peritoneal space,13,14 which can indicate ongoing hemorrhage if found following abdominal surgery. Of note, intra-abdominal fluid extravasation (IAFE) following hip arthroscopy occurs up to 15% to 30% of the time and is associated with increased pain 15–17. In severe cases, IAFE can result in hemodynamic instability and abdominal compartment syndrome (ACS) 18.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, intra-abdominal fluid extravasation (IAFE) following hip arthroscopy occurs up to 15% to 30% of the time and is associated with increased pain. [15][16][17] In severe cases, IAFE can result in hemodynamic instability and abdominal compartment syndrome (ACS). 18 However, unlike free fluid or blood, as seen after abdominal surgery, if the patient is hemodynamically stable postoperatively, there is no longer a risk of ongoing hemorrhage with hip arthroscopy.…”
Section: Introductionmentioning
confidence: 99%